Anisotropic and dielectric properties of TlSbSe2 chalcogenide compounds - Bas, H.; Kalkan, N.; Deger, D. (SPRINGER, 2016)
A comprehensive analysis of the electrical conductivity of TlSbSe2 layered compounds prepared using the Bridgman-Stockbarger technique is presented. The temperature dependence of the electrical conductivity of TlSbSe2 and its anisotropy (as measured parallel and perpendicular to the layers) was studied for temperatures between 233 and 353 K. We show that the anisotropy of the electrical conductivity is temperature dependent. The ratio alpha of the conductivities parallel and perpendicular to the layers obeys an exponential law, with a barrier height of about 37 meV. The dielectric constant and dielectric loss of TlSbSe2 were determined using ohmic Au electrodes in the frequency range 10 Hz-100 kHz and within the temperature interval 233-373 K. The dielectric constant and the dielectric loss are found to decrease with increasing frequency and increase with increasing temperature. These behaviors are due to the polarization mechanisms in the samples. Lastly the activation energy values were derived from dielectric measurements.
Keywords: CONDUCTION; DEPENDENCE; CRYSTALS; GROWTH; Engineering; Materials Science; Physics